Les léporidés et les petits carnivores de l'Igue du Gral ... - Mallye, Jean-Baptiste; Pelletier, Maxime (Zenodo, 2024)
Leporids and small carnivores at the Igue du Gral.- This work provides the outcome of the analysis of the remains of Leporidae and small carnivores that were identified at the Igue du Gral. We were able to identify the remains of the mountain hare and brown hare, wild rabbit, red fox and isatis, wolverine, badger, polecat, weasel and ermine. Once the integrity of the bone assemblage had been assessed in relation to the different excavation methods used, we characterised all these taxa from the biological point of view (size, age and sex), the relative conservation of the skeletons and their dislocation, and their distribution in the excavated volume both horizontally and vertically. In the light of these results and the radiocarbon dating carried out, it was possible to propose a biostratigraphy of the deposit and to discuss the palaeoenvironments of this region of Quercy. It was also possible to test the availability of small game to hunter-gatherers who frequented the region during the Late Palaeolithic. ...